Hispaniens Reichtum. Seine Rolle bei der römischen Eroberung der Iberischen Halbinsel und während der Republik bis auf Caesar - Koch, Michael (Madrider Mitteilungen, 2021)
This paper deals with Rome’s possible motives for the conquest of the whole of the Iberian Peninsula after the defeat of the Carthaginian colonial government in southern Spain, modern Andalusia. It resumes, too, modern controversial discussion about whether Roman politics considered the annexation of Spain a necessity for self-defence or a chance of enrich- ment. The author’s conclusion is, that after the defeat of Hannibal Spain meant no danger any more and that her annexation is due to Rome’s ideological convinctions of conquering and domination and due as well to the greed of the Roman aristocracy for honours, fame and booty.